Suppose p , q , and r are three mutually perpendicular unit vectors.
Vector u satisfies the equation p × ( ( u − q ) × p ) + q × ( ( u − r ) × q ) + r × ( ( u − p ) × r ) = 0
What is u in terms of p , q , and r ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Usually for such questions, it generally helps to evaluate the direction in terms of p , q , r directly. For example, take the dot product with respect to p , and then use the fact that a ⋅ ( b × c ) = b ⋅ ( c × a ) = c ⋅ ( a × b ) . The first term is 0, the second term is p ⋅ q × ( ( u − r ) × q ) = ( ( u − r ) × q ) ⋅ ( p × q ) = ( ( u − r ) × q ) ⋅ r = r ⋅ ( ( u − r ) × q ) = ( u − r ) ⋅ ( q × r ) = ( u − r ) ⋅ p . The third term is p ⋅ r × ( ( u − p ) × r ) = ( ( u − p ) × r ) ⋅ ( p × r ) = ( ( u − p ) × r ) ⋅ ( − q ) = − q ⋅ ( ( u − p ) × r ) = − ( u − p ) ⋅ ( r × q ) = ( u − p ) p ˙ .
Thus, ( 2 u − r − p ) ⋅ p = 0 which implies that the direction of u in terms of p is 2 1 .
Excellent solution. Evenly thought out
Problem Loading...
Note Loading...
Set Loading...
Using the notion of the vector triple product, we can say that \[\begin{array}{} \vec{p} \times \left( (\vec{u} -\vec{q}) \times \vec{p} \right) & =(\vec{p} \cdot \vec{p}) (\vec{u}-\vec{q}) -\left( \vec{p} \cdot ( \vec{u}-\vec{q} ) \right)\vec{p} \\ & =| \vec{p} |^2 (\vec{u}-\vec{q})-\left( \vec{p} \cdot \vec{u} -\vec{p} \cdot \vec{q} \right) \vec{p} \\ & =| \vec{p} |^2 (\vec{u}-\vec{q})-\left( \vec{p} \cdot \vec{u} \right) \vec{p} \quad \quad [\because \vec{p} \cdot \vec{q} =0] \end{array} \] Similarly we get q × ( ( u − r ) × q ) = ∣ q ∣ 2 ( u − r ) − ( q ⋅ u ) q r × ( ( u − p ) × r ) = ∣ r ∣ 2 ( u − p ) − ( r ⋅ u ) r
Substituting the above values, our equation now reads
∣ p ∣ 2 ( u − q ) − ( p ⋅ u ) p + ∣ q ∣ 2 ( u − r ) − ( q ⋅ u ) q + ∣ r ∣ 2 ( u − p ) − ( r ⋅ u ) r = 0 Since we are given that ∣ p ∣ 2 = ∣ q ∣ 2 = ∣ r ∣ 2 = 1 , our equation now becomes 3 u − p − q − r = ( p ⋅ u ) p + ( q ⋅ u ) q + ( r ⋅ u ) r − − − ( 1 ) As p , q , r are mutually perpendicular to each other, we can express u = λ 1 p + λ 2 q + λ 3 r , as a linear combination of p , q and r . Taking its scalar product with p , we get \[ \begin{array}{} \vec{u} \cdot \vec{p} & =\lambda_1 (\vec{p} \cdot \vec{p})+\lambda_2 (\vec{p} \cdot \vec{q} )+\lambda_3 (\vec{p} \cdot \vec{r}) \\ &=\lambda_1 |\vec{p}|^2+0+0=\lambda_1 \end{array} \]
Hence we obtained λ 1 = u ⋅ p . In the same manner, we get λ 2 = q ⋅ u and λ 3 = r ⋅ u . Now with the expression of linear expression, we get u = ( p ⋅ u ) p + ( q ⋅ u ) q + ( r ⋅ u ) r . Substituting this value into the equation (1), we have 3 u − p − q − r = u ⇒ 2 u = p + q + r
Hence we reached to the conclusion that u = 2 p + q + r .